posted by Ana on .
how do i solve these two problems?
3log(base5)^(x^2+9)-6 = 0
log(base8)^(n-3) + log(base8)^n+4)= 1
can you tell me step by step as well as the answers? please and thank you
Here is how to do the first one. The second is similar. First simplify the algebra. Then write the log equation in a different form.
3 log(base5)^(x^2+9) = 6
log(base5)^(x^2+9) = 2
Which is another way of saying:
5^2 = 25 = x^2 + 9
x^2 = 16
x = + or - 4
how'd you get the log(base5)^(x^2+9) = 2 ?
I divided both sides of the first equation by 3. It's a perfectly "legal" operation when dealing with algebraic equations.